El control de la actividad registral cooperativa: estudio crítico sobre sus dificultades e incógnitas - BURZACO SAMPER, María (REVESCO. Revista de Estudios Cooperativos, 2009)
The configuration of the Registries of Cooperatives as administrative instruments with legal effect, raises a series of difficulties of doubtless practical importance. Out of them, we can underline one: the control behind the registration activity. In this sense, the multiplying number of norms that shape current legal cooperative scene, may involve many divergent resolutions that, on top of the issues caused behind a potential excess of competence, may also has consequences on both the legal security as well as on the nature and reach of the judicial control. On the other hand, the hybrid character of the Registries of Cooperatives may need some adjustments whose solution is not always clear, due to the legal and legitimate assessments mismatching some restrictions of the applicable general administrative norm. This can be illustrated behind the registry principle of legitimacy, related to those mechanisms of administrative control which start formally relies on the Public Administration.